(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2023)
An estimated 2.6 million stillbirths occur annually. The vast majority of stillbirths, 84 per cent, occur in low and lower middle-income countries. Despite the large number of stillbirths worldwide, the topic of stillbirths in developing countries has received very little research, programmatic or policy attention. The loss of a wanted baby at any gestation is distressing, not only to the expectant parents but also to their relatives and the attending obstetrician. Every New-born Action Plan (ENAP) 2014 Global target was: 10 or fewer stillbirths per 1000 total births in all countries by 2030 and 8 or fewer stillbirths per 1000 total births in all countries by as global average and call to action to end preventable stillbirths 2030. To end the preventable stillborn or to achieve the aim of ENAP within 2030, 90% mothers need to receive 4 or more antenatal care by 2025, respectful maternal care during intrapartum with close monitoring and referral facilities for emergency obstetric care & newborn resuscitation need to be ensured. Institutional deliveries need to be increased and at least PNC for 80% women within 2 days of delivery should be ensured. Optimizing nutrition, screening infections and controlling preeclampsia, GDM, and obesity should be the priority. We must work all together to eliminate this tragedy of stillbirth. Search Web MED, Cochrane database, UpToDate, Pub Med, WHO. Bangladesh J Obstet Gynaecol, 2021; Vol. 36(1): 57-64